166k views
2 votes
Use complex conjugates to factor the expression
9x^2+36.

User Siva
by
4.9k points

1 Answer

2 votes

Answer:


9x^2+36=9(x+2i)(x-2i)

Explanation:

We have the expression:


9x^2+36

We can factor this using complex conjugates. Essentially, we will use the difference of two squares:


a^2-b^2=(a-b)(a+b)

First, we can factor out a 9 from our expression. This gives us:


9(x^2+4)

We can now rewrite our expression as:


9(x^2-(-4))

Therefore, our a² is
x^2 and our b² is -4.

Let’s solve for each of them individually. So, for a:


a^2=x^2

Take the square root of both sides:


√(a^2)=√(x^2)

Simplify:


a=x

And for b:


b^2=-4

Take the square root of both sides:


√(b^2)=√(-4)

Simplify:


b=√(-4)

Simplify the negative root using i:


b=√(-4)=√(-1\cdot4)=√(-1)\cdot√(4)=i√(4)=2i

Therefore, we have
a=x and
b=2i.

So, by using the difference of two squares:


9x^2+36=9(x+2i)(x-2i)

User Vol
by
5.6k points